Insights into the unique characteristics of hepatitis C virus genotype 3 revealed by development of a robust sub-genomic DBN3a replicon - Ward, Joseph C.; Bowyer, Sebastian; Chen, Shucheng; Campos, Guilherme Rodrigues Fernandes [UNESP]; Ramirez, Santseharay; Bukh, Jens; Harris, Mark (Microbiology Soc, 2020)
Hepatitis C virus (HCV) is an important human pathogen causing 400 000 chronic liver disease-related deaths annually. Until recently, the majority of laboratory-based investigations into the biology of HCV have focused on the genotype 2 isolate, JFH-1, involving replicons and infectious cell culture systems. However, genotype 2 is one of eight major genotypes of HCV and there is great sequence variation among these genotypes (>30% nucleotide divergence). In this regard, genotype 3 is the second most common genotype and accounts for 30% of global HCV cases. Further, genotype 3 is associated with both high levels of inherent resistance to direct-acting antiviral (DAA) therapy, and a more rapid progression to chronic liver diseases. Neither of these two attributes are fully understood, thus robust genotype 3 culture systems to unravel viral replication are required. Here we describe the generation of robust genotype 3 sub-genomic replicons (SGRs) based on the adapted HCV NS3-NS5B replicase from the DBN3a cell culture infectious clone. Such infectious cell culture-adaptive mutations could potentially promote the development of robust SGRs for other HCV strains and genotypes. The novel genotype 3 SGRs have been used both transiently and to establish stable SGR-harbouring cell lines. We show that these resources can be used to investigate aspects of genotype 3 biology, including NS5A function and DAA resistance. They will be useful tools for these studies, circumventing the need to work under the biosafety level 3 (BSL3) containment required in many countries.
Keywords: hepatitis C virus; sub-genomic replicon; genotype 3; NS5A